Analysis of the Influence of Asset Ratio, Working Capital Ratio, and Cost Efficiency Ratio on Financial Performance Ratio in Commercial Banks in Indonesia in 2017 - Millah, Fahmi Syaeful; Zaharuddin, Zaharuddin; Purnomo, Hadi (Asian Journal of Management Analytics, 2025)
The Banking Industry plays an important role for economic development as a Financial Intermediary or intermediary for parties with excess funds and those who need funds. Banks are an industry whose main activity is the collection of funds from the public and then channeling them with the aim of earning income. It is important for banks to maintain public trust. The purpose of this study is to find out and get information about the Analysis of the Effect of Working Capital Ratio (expressed by Capital Adequacy Ratio/CAR, Net Interest Margin /NIM), Cost Efficiency Ratio (Operating Cost versus Operating Income/BOPO), Asset Ratio (Net Performing Loans/NPL, Loan to Deposit Ratio/LDR to Financial Performance Ratio/ Return On Assets/ROA for Commercial Banks on 2017, and to find out how much influence working capital ratios, cost efficiency ratios and bank assets to commercial bank financial performance ratios in Year 2017 Type of Descriptive Quantitative Research,, Data collection techniques using saturated data sampling where all members of the population are used as samples, which means the sample used is the same as the population.